Partial factors for the design resistance of composite beams in bending. (February 2015) - Hicks, Stephen J.; Pennington, Andrew
Abstract: This paper presents the results from a reliability analysis of the resistance of composite beams in sagging bending designed according to Eurocode 4. Using the EN 1990 methodology, the partial factors γ M for the structural steel, concrete and shear connection were evaluated. The present study extends earlier work by considering geometrical tolerances given within the published European product and execution standards, which were unavailable during the original calibration of Eurocode 4. Furthermore, recently reported European production data on the yield strength of structural steel is also included. The analyses consider test data from 164 beams with full shear connection, partial shear connection, ductile connectors, non-ductile connectors and beams with high strength steel, which ar?e supplemented with over 3 million simulations. It was found in the present work that the current recommended values for γ M were only justified for beams with full shear connection. For beams with partial shear connection, the calculated values of γ M were larger than recommended because the partial factor associated with the uncertainty of the resistance model varied considerably. To remedy this situation, conversion factors that are a function of the overall composite beam depth are proposed which, when applied to the design models, justifies lower partial factors than that currently recommended by Eurocode 4. Highlights: Reliability analysis of Eurocode 4 according to EN 1990 Partial factors evaluated for the current design methodologies given in Eurocode 4 Partial factor γ Rd proportional to the overall composite beam depth New conversion factors justify lower partial factors than recommended by Eurocode 4.